PENGANGGARAN BERBASIS KINERJA PADA PEMERINTAH DESA CUPAK KABUPATEN JOMBANG - Irda Agustin Kustiwi; Tri Ratnawati (Universitas Sains dan Teknologi Komputer, 2023)
Village fund and budget programs are activities carried out by the central government to develop Indonesia in developing village potential by empowering the local economy to realize community independence and create sustainable, independent villages. Cupak village, Ngusikan sub-district, Jombang district is one of the villages that has the potential for a religious tourism village, part of the villages assisted by the Higher Education Matching Fund by the accounting study program at the University of 17 August 1945 Surabaya. This village has a phenomenon that shows a level of independence in the management of the budgeting process that is still lacking by the local government. This explains the need for internal audits in the process of improving regional finances so that they can be used properly by both the regional government and the community. The research team chose a qualitative approach to produce internal audit results regarding the budgeting process and fund allocation in the Cupak religious tourism village, Jombang. They will also provide advice to interested parties. Researchers hope that the government and the community of Cupak village, Jombang will be involved in the process of preparing, implementing and being accountable for village fund budgeting.